The Impact of Distinct Dopant Elements (Cu and Al) on the Electrochemical Characteristics of MgO Thin Films Formed Using the Electrodeposition Technique - Balkrishna J. Lokhande; Mahadev T. Mhetre (International Journal of Electro-Mechanics and Material Behaviour, 2024)
By using an aqueous electrodeposition technique, copper (Cu) and aluminum (Al) doped magnesium oxide (MgO) thin films were created. We examined how the dopant elements affected the electrochemical characteristics of MgO thin films deposited on stainless steel (SS) substrates in the current study. We annealed the MgO-based films at 450◦C. The MgO films doped with Cu and Al have been determined by X-ray diffraction (XRD) results. Cyclic voltammetric analyses (CV), galvanostatic charge-discharge (GCD) technique, are the electrochemical methods. The redox behavior of both Cu and Al-doped and pristine MgO during the CV is confirmed by peaks in the CV curves. There was a maximum of 24.16 Fg-1 in the measured specific capacitance (SC) of Al-doped MgO. In contrast to typical capacitors, GCD analysis reveals distinct behavior. The charging and discharging times were found nearly the same for different applied currents.
Keywords: Cyclic voltammetric analyses; EDLC; Electrodeposition technique; elements; medical devices